Exploring the Impact of Digital Technology on Employee Adaptation and Organizational Performance - Fahrul Kahfi (Journal of Management and Administration Provision, 2022)
The present research endeavors to examine the influence of digital technology on the adjustment of employees and the performance of organizations. In contemporary times, the imperative for organizations to maintain competitiveness necessitates digital transformation. Consequently, it is essential to comprehend the impact of digital technology on employees. The research utilizes a mixed-methods methodology to gather and evaluate information from both employees and managers in diverse organizations. The findings suggest that the utilization of digital technology has a noteworthy influence on the productivity, efficiency, and flexibility of employees. Consequently, organizations can reap advantages by adopting digital technology to enhance their overall performance. Notwithstanding, the workforce encounters obstacles in acclimating to novel technologies, thereby requiring efficacious change management tactics such as instruction and assistance. The research emphasizes the significance of proficient communication, cooperation, and a conducive environment in advancing prosperous digital conversion. Furthermore, it underscores the importance of proficient execution and administration of digital technology in order to achieve advantages such as heightened efficiency, productivity, and innovation. The results offer direction for entities undergoing digital metamorphosis, encompassing the significance of allocating resources towards employee education and advancement, fostering a culture that is supportive and collaborative, and proficiently executing and overseeing digital technology. In general, this research adds to the expanding literature on the influence of digital technology on the work environment and underscores the necessity for companies to adjust and develop in order to sustain their competitiveness.